Isometric Tunnel Placement in Ulnar Collateral Ligament Reconstruction with Single CT Scan - Kholinne, Erica (Biomed Res Int, 2017)
BACKGROUND: Isometric tunnel placement for anterior bundle of the medial collateral ligament (MCL) reconstruction is mandatory for successful surgery. PURPOSE: This study aimed to demonstrate a useful method for identifying isometric tunnel placement using a single computed tomography (CT) scan. STUDY DESIGN: Descriptive Laboratory Study. METHODS: Five normal elbows were scanned at 4 different flexion angles at 45° increment. Three-dimensional models were analyzed using 2 different approaches: single and multiple CT scans methods. Ligament footprints in the humerus and the ulna were registered. Ligament length and isometric points were defined. The locations of the isometric points were imported into both methods to be compared. RESULTS: There was no significant difference between 2 methods in calculating the length in every zone. There was also no significant difference in determining isometric ligament's origin point, which is located approximately 18.2 ± 4.0 mm and 18.4 ± 2.9 mm for single and multiple CT, respectively, measured inferolaterally from medial epicondyle. CONCLUSIONS: A solid preoperative plan is critical when predicting tunnel locations due to the difficulty in finding isometric points and the individuality of optimal bone tunnel locations. Using single CT scan, optimal locations can be predicted with the same accuracy as a multiple CT scans with less radiation exposure.